Indoor air quality sensors data mapped to students behavior in classroom through production rules technique - Nor Azhar, Ahmad; Fauziah, Zainuddin; Roslina, Abd Hamid; Rahmah, Mokhtar (2019)
The behavior of students in a classroom is hardly being recognized by the instructor. Recent development, a researcher determines these traits by using a permissive approach. In this paper, a real-time classroom environment using sensing device with detection of student behavior is proposed. Recent studies as guidelines for this paper lead to three early hypotheses; development of the engine to detect student’s behavior based on environmental sensing, faster production rules and reliability using economical sensors. The production rules are created step by step based on expert endorsements in three different areas; environmental, health, and education. The test beds are three classrooms with separate periods had been deployed to proof the hypotheses. The result shows a promising output, which is all hypotheses are fully accepted.